1994
DOI: 10.2166/wst.1994.0249
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nitrification-denitrification potential of istanbul domestic wastewaters

Abstract: This paper summarizes experimental evaluations on Istanbul domestic wastewaters with respect to their potential of biological nitrogen removal. Characterization studies involve together with relevant carbonaceous and nitrogenous wastewater components, significant rate coefficients affecting aerobic and anoxic processes. Experimental results indicate a low biodegradable carbon to nitrogen ratio and a relatively small readily biodegradable COD fraction. A new method is introduced to determine maximum specific gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 0 publications
5
26
0
2
Order By: Relevance
“…The mechanistic model adopted for the study involved a structure compatible with the selected organic substrate and the observed utilization mechanisms: it accounted for the fact that acetate would be readily utilized without an auxiliary hydrolysis mechanism, generally defined for most wastewaters (Orhon et al, 1994 it also included substrate utilization processes both for direct microbial growth and intracellular storage (Karahan-Gul et al, 2002). This way, the adopted structure of the model involved four microbial processes, namely, microbial growth on acetate; storage of acetate as polyhydroxy butyrate, (PHB); secondary growth on stored PHB and endogenous respiration.…”
Section: Model Structurementioning
confidence: 99%
“…The mechanistic model adopted for the study involved a structure compatible with the selected organic substrate and the observed utilization mechanisms: it accounted for the fact that acetate would be readily utilized without an auxiliary hydrolysis mechanism, generally defined for most wastewaters (Orhon et al, 1994 it also included substrate utilization processes both for direct microbial growth and intracellular storage (Karahan-Gul et al, 2002). This way, the adopted structure of the model involved four microbial processes, namely, microbial growth on acetate; storage of acetate as polyhydroxy butyrate, (PHB); secondary growth on stored PHB and endogenous respiration.…”
Section: Model Structurementioning
confidence: 99%
“…Based on the measurements of total OUR (OUR tot (t)), endogenous OUR (OUR end (t)) and degraded COD (COD degr. ), the Y H coefficient was determined from the following equation (Ekama et al 1986;Kappeler and Gujer 1992;Orhon et al 1994):…”
Section: Conventional Our Measurementmentioning
confidence: 99%
“…Certain factors should be taken into consideration while seeking an appropriate estimation method for µ H,max . and Orhon et al (1994b) proposed to use batch tests for determining µ H,max . Williamson and McCarthy (1975) developed a method called the infinite dilution procedure to estimate the substrate saturation coefficient, K S , along with the maximum substrate removal rate, r S,max .…”
Section: Maximum Specific Growth Rate For Heterotrophic Biomass µ Hmaxmentioning
confidence: 99%
“…The fraction of soluble COD that is readily biodegradable can be measured through the OUR in the continuous reactors Sollfrank and Gujer 1991;Witteborg et al 1996) as well as in the batch reactors Kristensen et al 1992;Orhon et al 1994b;Xu and Hasselblad 1997). It should be noted, however, that these methods are based on the approach proposed in ASM1 that the readily biodegradable COD is directly used for the growth of microorganisms without considering any storage phenomena.…”
Section: Characterization Of Individual Fractionsmentioning
confidence: 99%